2021
DOI: 10.1007/s11661-021-06252-2
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation Behavior of Conventional and Nb-Modified MAR-M246 Ni-Based Superalloy

Abstract: The present investigations focused on the thermal oxidation of two variants of MAR-M246 alloy having the same contents of Ta and Nb in at. pct, considering the effects of total replacement of Ta by Nb. The alloys were produced by investment casting using high purity elements in induction furnace under vacuum atmosphere. The alloys were oxidized pseudo-isothermally at 800°C, 900°C and 1000°C up to 1000 hours under lab air. Protective oxidation products growing on the surface of the oxidized samples were mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(37 reference statements)
4
5
0
Order By: Relevance
“…Nevertheless, bunsenite NiO and chromia Cr 2 O 3 oxides were detected in the sample oxidized for 240 h. In Figure 9b, which shows the low‐intensity peaks in detail, Al 2 O 3 , TiO 2 and XY 2 O 4 phases (with Cr 2 CoO 4 structure—cubic Fd‐3m) are also detectable, in consonance with the thermodynamic simulations. Alkmin et al [ 16 ] found mainly Al 2 O 3 , Cr 2 O 3 , TiO 2, and spinels such as CoCr 2 O 4 and NiCr 2 O 4 on the MAR‐M246 alloy after pseudo‐isothermal oxidation at 800°C for 1000 h, in good agreement with the results presented here.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, bunsenite NiO and chromia Cr 2 O 3 oxides were detected in the sample oxidized for 240 h. In Figure 9b, which shows the low‐intensity peaks in detail, Al 2 O 3 , TiO 2 and XY 2 O 4 phases (with Cr 2 CoO 4 structure—cubic Fd‐3m) are also detectable, in consonance with the thermodynamic simulations. Alkmin et al [ 16 ] found mainly Al 2 O 3 , Cr 2 O 3 , TiO 2, and spinels such as CoCr 2 O 4 and NiCr 2 O 4 on the MAR‐M246 alloy after pseudo‐isothermal oxidation at 800°C for 1000 h, in good agreement with the results presented here.…”
Section: Resultssupporting
confidence: 91%
“…The phases observed were Ni-gamma, Cr 2 O 3 , Al 2 O 3 , NiO, rutile-TiO 2 , XYO 4 (structure from WNiO 4 -monoclinic P2/c) and XY 2 O 4 (again related to (Cr, Co) 3 O 4 structurecubic Fd-3m), in line with the thermodynamic simulations, except for the TiO 2 and XYO 4 phase. Finally, Alkmin et al [16] showed that the main oxides formed on the MAR-M246 alloy after pseudo-isothermal oxidation at 1000°C for 1000 h were Al 2 O 3 , the spinel CoCr 2 O 4, and TiO 2 , also observed here.…”
Section: Xrd Analysissupporting
confidence: 79%
See 3 more Smart Citations